Pragmatic and manipulative potential of personal pronouns in political discourse - Gazarova, Diana (Bulletin of Yerevan University H: Russian Philology, 2022)
The article considers the pragmatic and manipulative of personal pronouns in political discourse. Despite the main deictic meaning, personal pronouns perform different functions in political discourse. Their main feature of pronouns is that they are the main factors of manipulating society. The choice of politics or other pronouns of the properties of various factors: political, geopolitical, social, psychological, etc. The use of pronouns makes the politician's speech more expressive and, what is the most important, more effective in the process of achieving the main goal of political discourse - a struggle for power/preservation of power. Personal pronouns express a wide variety of meanings in political discourse, up to the exact opposite. So, for example, the personal pronoun we can express both the idea of ​​unity and solidarity (inclusive we), and, conversely, the idea of ​​separation and distancing (exclusive we). Personal pronouns contribute to the implementation and explication of the dichotomy “friend or foe” - the most important component of political discourse. Personal pronouns have in political discourse evaluative connotations and express one of the main postulates of political discourse: “friend (we, ours) is good, and foe (they, theirs) is bad. Personal pronouns help the politician to inspire the people / electorate that the people's interests are taken into account; that the politician and the people are united, that they have common interests, and all this enhances the verbal and emotional impact on the electorate.
Keywords: discourse; personal pronouns; “friend or foe”; inclusive “we”; exclusive “we”